Ontology integration by semantic mapping for solving the heterogeneity problem - Mohammed, Moseed; Awanis, Romli; Rozlina, Mohamed (Springer Nature, 2023)
In recent years, ontology integration has received an increased focus in ontology engineering. Ontology integration is a complex process that has some difficulties such as semantic heterogeneity. The goal of this research is to use semantic mapping to reduce integration complexity and solve semantic heterogeneity. What is ontology engineering? What difficulties haven't been solved until now by ontology integration? What is the effective role of semantic mapping in semantic heterogeneity? This research seeks to address these questions. The expected contribution of this research is to build a comprehensive view of ontology integration and support interoperability. The significance of using semantic mapping to improve interoperability on ontology integration is confirmed by researchers.